In vivo time harmonic multiple frequency elastography of human liver - Tzschaetzsch, Heiko; Braun, Juergen; Fischer, Thomas; Klaua, Robert; Schultz, Michael; Sack, Ingolf (IEEE International Ultrasonics Symposium, IUS, 2012)
For diagnosis of fibrosis we developed an ultrasound elastography system. Which combines the advantages of magnetic resonance elastography (MRE) with ultrasound elastography (USE). Multi-frequency MRE has a high diagnostic power for the staging of low grades of fibrosis. USE has the potential to provide similar results in real-time and at low costs with a wide availability. We demonstrate the feasibility of time-harmonic multi-frequency USE at six volunteers and compare the resulting shear wave speed dispersion over seven frequencies with literature values from MRE © 2012 IEEE.
CRIS-Team Scopus Importer:2022-08-03
Keywords: dynamic elastography; in vivo; liver; multiple frequency vibration